BIBLIOMETRIC MAPPING PUBLICATIONS OF SCIENTIFIC WORK OF INFORMATION SYSTEMS LECTURER AT UIN SYARIF HIDAYATULLAH JAKARTA ON GOOGLE SCHOLAR SYSTEMATIC REVIEW USING RESEARCH RABBIT - Elvi Fetrina; Murni (JURNAL PERANGKAT LUNAK, 2024)
ABSTRACT In the modern era dominated by technology, understanding academic developments in the Information Systems Department of UIN Syarif Hidayatullah Jakarta through Google Scholar and Research Rabbit is very important. The research focuses on identifying lecturers' research interests, with the aim of developing a more relevant curriculum for students. Literature studies are used to collect and analyze information from various sources. The research results reveal the latest research topics that lecturers publish, becoming the basis for future research and guidelines for curriculum development according to technological developments. The conclusion emphasizes the importance of adapting research to technological developments and a deep understanding of lecturers' interests to maintain the relevance of the curriculum in an ever-changing academic world. This step is key in preparing students to succeed in a rapidly developing environment. In this context, lecturers' understanding and research helps shape a curriculum that is able to face the challenges of modern technology and produce graduates who are ready to face continuous change. Keywords : Bibliometrics, Publications, Scientific Work, Google Scholar, Research Rabbit